STOMACH CONTENT ANALYSIS OF MOTAN FISH (Thynnichthys thynnoidesBleeker) FROM THE TELUK PETAI LAKE, BULUH NIPIS VILLAGE, SIAK HULU SUBDISTRICT, KAMPAR REGENCY, RIAU PROVINCE. - Belgian Tambunan; Ridwan Manda Putra; Eddiwan Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Thynnichthys thynnoidesis one of freshwater fishes that inhabit the Teluk Petai lake.A research aim to understand the information on stomach content and it’s relationship with size, sex and environmental condition.This research has been done on March to April 2019. Fish samples were captured using sempirai and nets. Sampling was conducted 4 times in two months. Type of food present in the stomach content of fish was analyzed using a volumetric method and the IP (Index of Preponderance) was calculated. There were 95 fish captured. Result shown the feed of T. thynnoidesphytoplankton (Bacillariophyceae, Chlorophyceae, Cyanophyceae) and Zooplankton (Rotifera). The main food of T. thynnoideswasBacillariophyceae(57.62%). There was no differences in the main food of males and female fishes. The water quality parameter were as follows: temperature 30.5 0C, brightness 76.25 cm, pH 6, DO 6.44 mg/L, CO2 9.75 mg/L. Based on data obtained, it can be concluded that theT. thynnoides is an plankton feeder.Keywords:Thynnichthys thynnoides, StomachContentAnalysis, Index of Preponderance, TelukPetaiLake